Upaya Mendorong Pencapaian SDGs-12 melalui Sosialisasi Pemanfaatan Sampah Organik menjadi Eco Enzyme pada Masyarakat Desa Jelantik - Hasyim; Rohani; Saidah, Humairo; Yasa, I Wayan; Wiradharma, Lalu Wirahman; Suroso, Agus; Supriyadi, Anid; Karyawan, I Dewa Made Alit; Negara, I Dewa Gede Jaya (Universitas Mataram, 2024)
The Jelantik Village community still faces environmental problems, especially the problem of waste generation that disrupts environmental comfort. The limited capacity of the village government and the low level of community knowledge in processing waste are the main causes of this problem. So, this community service activity aims to disseminate information about processing organic waste into eco enzyme, which is beneficial and simple in procedures. Socialization is carried out using a counseling method on how to make eco enzyme using fruit/vegetable waste mixed with sugar and water in a ratio of 3:1:10. This counseling has eco enzyme carried out and attended by at least 30 participants. The team has delivered counseling on how to select materials, the process of making eco enzyme, and how to utilize it. The team informed the Jelantik Village community about the principles and stages of making eco enzyme correctly so the community can practice it to process their waste at home. This activity is expected to increase community knowledge while reducing waste problems, producing beneficial eco enzyme, and promoting SDGs-12 achievement.